FORMULASI PENGATURAN PAJAK PENGHASILAN ATAS PENYETORAN MODAL (INBRENG) TANAH DAN/ATAU BANGUNAN KE DALAM PERSEROAN TERBATAS - Mustofa Mustofa; Rachmad Syafa'at; Bambang Winarno (VERITAS, 2017)
This journal discusses the existence of differences in tax treatment in the Income Tax Act which in Article 4 paragraph (1) letter d number 1 with Article 4 paragraph (3) letter c on payment of capital stock other forms (inbreng) in the form of land and / or buildings. According to Article 4 Paragraph (1) letter d number 1 Income Tax Law, payment of capital stock other forms (inbreng) in the form of land and / or buildings will give rise to an obligation to pay income tax, as included in the category of rights of 2.5% of the gross amount. Whereas Article 4 paragraph (3) letter c Income Tax Act, that the payment of capital stock other forms (inbreng) in the form of land and / or buildings are not subject to income tax. The method used in this research is using normative juridical, with the approach of the Law and Conceptual Approach. Based on the results of research conducted, that the Income Tax Act Article 4 paragraph (3) letter c, treasure inbreng received by company (PT. Trio Warna Gempita) is not a taxable income not including the alias object Income Tax (PPh). Because not explicitly mentioned in the Income Tax Act. Authors relate to the principle-deductibility taxability or non taxability principle of non deductibility adopted by the Income Tax Act, then this treatment can logically acceptable.